Bay City blues - Chandler, Raymond, 1888-1959.; Krasko, Jan. (Warszawa : Da Capo, 1993)
Polish translations of three mysteries by a master of the genre.
Bay City blues -- Uzywka profesora Binga -- Spizowe drzwi.
Keywords: Detective and mystery stories, American -- Translations into Polish